Clinical Profile of Dengue Fever in Children: A Study from Southern Odisha, India - Shubhankar Mishra; Ramya Ramanathan; Sunil Kumar Agarwalla (Scientifica)
Background. In India, dengue epidemics are becoming more frequent (WHO, 2008). The majority of dengue viral infections are self-limiting, but complications may cause high morbidity and mortality. Objectives. To assess the clinical profile of the dengue infection in children less than 14 years of age and to evaluate the outcomes of dengue fever from September 2013 to August 2015 at the Pediatric Department of Maharaja Krishna Chandra Gajapati Medical College, the largest tertiary care hospital of southern Odisha. Results. A total of 97 cases were classified into 84 (86.59%) nonsevere and 13 (13.40%) severe dengue cases. The most common age of presentation was above 11 yrs. The mean age of admission was 8.7 yrs. The most common presenting symptom was fever seen in 100% and hepatomegaly (43.8%), the most common physical finding. Gastrointestinal bleeding was markedly seen in severe dengue (76.9%). Elevation in aspartate transaminase (SGOT) was found in 47.42% and thrombocytopenia in 27.5%. The correlation between hepatomegaly and elevated SGOT was significant (P value 0.0346). Case fatality rate (CFR) was 1.03%. The mean duration of hospitalisation was 3.8 days. Conclusion. In children, if symptoms like fever, pain, rashes, and vomiting are associated with hepatomegaly and elevated SGOT in context of low TPC, a strong possibility of dengue fever is present, especially in an epidemic setting. Early suspicion and effective management can reduce the severity.